Phenomenological Study: Overview of Palliative Management in The Pre-Hospital Area of Semarang City - Kristianto Dwi Nugroho; Sri Hartini Mardi Asih; Swanny Trijanti Widyaatmadja (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2022)
Background: Palliative care is holistic care that is patient-centered and comprehensive both to the family and those closest to the client, which is carried out as early as possible. End-of-life preparation requires coordination from disciplines, including pre-hospital services, which are at the forefront of providing emergency services. So that the integration of palliative and pre-hospital nursing needs to be done. Purpose: To find out the description of palliative patient management in the prehospital area. Methods: This study is a qualitative study with a phenomenological approach to see the description of palliative services in the pre-hospital area of Semarang city. 7 Participants were involved in the research from 4 emergency ambulances and 3 ambulances on standby in the city of Semarang. In-dept interviews were conducted to explore the existing phenomena. Result: This study resulted in 13 themes, namely (1) Providing emotional support to patients and families, (2) Caring for the patient's condition, (3) Ambulance nurses' actions in dealing with palliative patients, (4) Collaboration with stakeholders, (5) Positive Impact the existence of pre-hospital services, (6) Feelings of pride as a pre-hospital nurse, (7) Feelings of satisfaction of nurses when they are successful in doing help, (8) Feelings of the doubt when families do not follow procedures, (9) Limited facilities and infrastructure, (10) Strategies to improve pre-hospital services, (11) Education to clients and families, (12) Lack of family support, (13), Patient motivation towards recovery. Conclusion: There has been an integration between palliative and pre-hospital nursing with a psychosocial approach in terminal patients. Deeper integration can be done with the more specific training of pre-hospital nurses on palliative care.